DESAIN E-LKPD BERBASIS PROBLEM BASED LEARNING TERINTEGRASI ETNOSAINS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PEMBELAJARAN IPAS FASE C - Susandra, Ratih Rintan (Jurnal Visi Ilmu Pendidikan, 2025)
IPAS learning in elementary schools often lacks contextual and engaging approaches, leading to low critical thinking skills. This study aims to develop an interactive E-LKPD based on Problem Based Learning (PBL) integrated with ethnoscience to improve students"™ critical thinking in IPAS. Using the Borg and Gall development model, the research involved expert validation, teacher and student trials, and effectiveness testing in several elementary schools in Kemusu, Boyolali. The E-LKPD received high validity (Aiken"™s V = 0.81), with positive practicality responses from teachers and students. Critical thinking tests showed a moderate improvement (N-Gain = 0.61), indicating that the E-LKPD helps students think critically through contextual and culturally relevant problems. The product is considered suitable for use in classrooms and supports 21st-century skills. Keywords: E-LKPD, Problem Based Learning, ethnoscience, critical thinking